New Town of Hashtgerd Cultural Planning - Negin Hojjati; Marjan Nematimehr (صفه)
The new town movement has been a solution provided by urban planners in response to the growing population of urban dwellers. The rapid growth of these towns and the emphasis of urban planners on their economic aspects alone debased them as dormitory towns that were facing social injustice and cultural issues only after a short while. This is because culture is one of the dimensions of sustainability, whose ignorance in planning procedures can actually fail sustainable development efforts. This research tried to make a link between urban planning and cultural planning by extraction of dimensions, criteria, and indicators of cultural planning according to which new towns in Iran could be evaluated. The most re-appearing dimensions of cultural planning which can be measured and evaluated were extracted from the existing body of native and foreign research utilizing content analysis. They are cultural sustainability (in both native and foreign sources), cultural vitality and cultural diversity (in foreign sources), identity and characteristic (in both native and foreign sources), and justice (in native sources). The weighting factors of the upper-level variables according to the results of the experts’ questionnaire were calculated using swing weighting, and subsequently the weight of each indicator was assigned. The calculated weights revealed that cultural sustainability and identity and characteristic with weights of 0.261 and 0.232, respectively, were the most important dimensions of cultural planning. The evaluation results in the New Town of Hashtgerd indicate that the central parts of the town have better cultural conditions, but the eastern and western parts of the city shall be improved in terms of cultural sustainability, justice, cultural diversity and cultural vitality. Among strategies suggested to be employed include creating services and land uses according to the needs of the growing population, equitable distribution of services, improvement of cultural activities, and increase in the share and improvement of public transportation.